The Effect of Solvency and Liquidity on Stock Prices Which is Moderate by Profitability - Nuraisiah, Rohaelis; Ismail, Tubagus; Hanifah, Imam Abu; Indriana, Ina (International Journal of Economics and Financial Issues, 2025)
This study aims to examine the influence of Solvency Ratio and Liquidity with Profitability as moderating variables on stock prices of manufacturing companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange (IDX). Profitability is measured using return on assets, solvability is measured using debt to equity ratio, liquidity is measured using current ratio, and stock price uses closing price. This study uses a quantitative research method. The population in this study are manufacturing companies in the food and beverage sub-sector listed on the IDX. This study does not use samples but uses the entire population that has been given criteria, namely 26 companies. The research data was taken for 6 years, from 2018 to 2023, resulting in 136 data processed. The analysis method used is moderated regression analysis (Moderated Regression Analysis) using the SPSS 26 program. The results of this study indicate that liquidity has a significant effect on stock prices, while solvency does not significantly affect stock prices. The results of the moderating variables show that Profitability cannot moderate the influence of liquidity and solvency on stock prices.